Movimientos sociales, acción colectiva y planificación participativa en el Brasil - De Azevedo, Sergio; Pereira Prates, Antonio Augusto (Revista EURE - Revista de Estudios Urbano Regionales, 1995)
The paper aims at discussing the meaning of urban associativism in the setting of the political relationships between the peripherals populations of the large cities and the states. It encompasses the governmental actions known as participative planning. In this first part of the paper the dominant paradigm in the studies of urban social movements in Brazil is reviewed. It is showed that the noncritical use of a Marxist model impairs the analysis. Consequently fundamental matters related to the urban associativism phenomena are reglected, such as those emphasized by the collective action literature the relationships between the political actorÍ€™s interest, the individual rationally and the collective actions, as well as the Michelsean organizational logic, the solidarity systems and the types of collective action. The second part of the paper deals with participative planning. First of all, a retrospect of Brazilian history is provided showing the path of centralization to decentralization in the local government history. The paper criticizes the current Brazilian sociological literature arguing that it treats distinct social phenomena under the label of participative planning as if they were homogeneous ones. Drawing in empirical evidence from local government case studies, the authors try to demonstrate that the so-called participative planning hides two different types of popular participation in the communities: the first one is denominated as Í€œrestrict or instrumental participationÍ€ and the second one as Í€œwide or neo-corporatist participationÍ€. Finally, the authors analyze the problems, potentialities and constraints of popular participation in Brazilian loci governments. Í